Accelerometers can measure total and activity-specific energy expenditures in free-ranging marine mammals only if linked to time-activity budgets - Jeanniard-Du-Dot, Tiphaine; Guinet, Christophe; Arnould, John P.Y.; Speakman, John R; Trites, Andrew W. (Functional Ecology, 2017)
International audience 1. Energy expenditure is an important component of foraging ecology, but is extremely difficultto estimate in free-ranging animals and depends on how animals partition their timebetween different activities during foraging. Acceleration data have emerged as a new way todetermine energy expenditure at a fine scale but this needs to be tested and validated in wildanimals.2. This study investigated whether vectorial dynamic body acceleration (VeDBA) could accuratelypredict the energy expended by marine predators during a full foraging trip. We alsoaimed to determine whether the accuracy of predictions of energy expenditure derived fromacceleration increased when partitioned by different types of at-sea activities (i.e. diving, transiting,resting and surface activities).3. To do so, we equipped 20 lactating northern (Callorhinus ursinus) and 20 lactating Antarcticfur seals (Arctocephalus gazella) with GPS, time-depth recorders and tri-axial accelerometersand obtained estimates of field metabolic rates using the doubly labelled water (DLW)method. VeDBA was derived from tri-axial acceleration, and at-sea activities (diving, transiting,resting and surface activities) were determined using dive depth, tri-axial acceleration andtravelling speed.4. We found that VeDBA did not accurately predict the total energy expended by fur sealsduring their full foraging trips (R2 = 036). However, the accuracy of VeDBA as a predictorof total energy expenditure increased significantly when foraging trips were partitioned byactivity and when activity-specific VeDBA was paired with time-activity budgets (R2 = 070).Activity-specific VeDBA also accurately predicted the energy expenditures of each activityindependent of each other (R2 > 085).5. Our study confirms that acceleration is a promising way to estimate energy expenditures offree-ranging marine mammals at a fine scale never attained before. However, it shows that itneeds to be based on the time-activity budgets that make up foraging trips rather than ...